Pengembangan Media Animasi dalam Model Pembelajaran STAD Materi Sistem Peredaran Darah Manusia di SMP - Nadila Eka Okta Cahyaningrum; Zainul Abidin; Agus Wedi (Jurnal Kajian Teknologi Pendidikan, 2022)
The development of animation media in the learning model STAD aims to create effective and attractive learning activities so as to improve student learning outcomes. The animation media was developed in learning the human circulatory system in junior high schools. The research method used the Sadiman development model. Product validation is carried out by material experts and media experts. Meanwhile, the target of the field evaluation was class VIII students of SMP Negeri 1 Kauman Ponorogo. Based on the results of the field evaluation, it can be concluded that the animation media in the learning model STAD, the human circulatory system material, is categorized as suitable for use in learning activities. Furthermore, based on the results of the pre-test and post-test that were tested using the Paired Sample T-Test, it was found that there was a difference between the pre-test and post-test results. So it can be concluded that the use of animation media in the learning model STAD for the human circulatory system material in SMP can be applied as a guide in learning activities by teachers to create effective and interesting learning so that it can improve learning student’s outcomes.